PERTUMBUHAN PUYUH (Coturnix coturnix japonica) SETELAH PEMBERIAN TEPUNG KUNYIT (Curcuma longa L.) PADA PAKAN - Widyastuti, Wuri; Mardiati, Siti Muflichatun; Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Quail have the ability to grow and reproduce very quickly that at the age of 42 days. The aims of the research was to know the potential of turmeric powder as a feed additive to improve growth quail. This study used 60 quails consists of Â 4 treatments and 5 replications, namely P0 : as a control, a group of quail feed a standard concentrate, P1 : quail groups were given a dose of turmeric powder with 13,5 mg/quail/day, P2 : group quail were given a dose of turmeric powder with 27 mg/quail/day, and P3 : quail groups were given a dose of turmeric powder with 54 mg/quail/day. Each repeat consists of 3 quails are placed in a cage. Treatment begins at 3 weeks old quail until 2 month. Research using a completely randomized design. Parameters measured were feed consumption, water consumption, the length of the wing, the length of the femur, the length of Â the tibia tarsus and the length of the tarso metatarsus. Data obtained from this study were analyzed using ANOVA ( Analysis of Varian ) at the level of 95 %. The result shows was not differences in feed consumption, water consumption, the length of the wing, the length of the femur, the length of the tibia tarsus and the length of the tarso metatarsus. Conclusion of this study Â is the provision of turmeric powder in the feed does not have the potential to increase the growth of quail